An interdisciplinary, collaborative CURE to investigate mutagen-sensitive alleles in Drosophila melanogaster - Marissa Howard; Elyse Bolterstein; Kathryn P. Kohl; Eric P. Stoffregen; Christina I. Swanson (Journal of Microbiology & Biology Education)
ABSTRACT Course-based undergraduate research experiences (CUREs) are an effective strategy to teach students about the process of scientific research. Students participating in a CURE also benefit in numerous other ways, such as gaining increased enthusiasm for science and increased retention in a STEM field. Because scientific research is increasingly interdisciplinary and collaborative, recently developed CUREs have begun to incorporate interdisciplinary approaches and networking components. Interdisciplinary, networked CUREs have, in several cases, expanded learning gains for participating students beyond the benefits of traditional CUREs. Here, we describe a novel interdisciplinary, collaborative CURE. Our CURE was launched with four participating primarily undergraduate institutions (PUIs) and the broad research goal of characterizing mutagen-sensitive alleles in Drosophila melanogaster. Student surveys suggest that our CURE has successfully contributed to learning gains across a variety of areas, including increased project ownership, increased experience with collaboration, and increased experience with interdisciplinary research. Furthermore, participating faculty have benefitted from increased scholarly productivity. Our CURE could be expanded to include additional institutions, or could serve as a model for PUI faculty interested in developing their own collaborations as a strategy to tackle broad, interdisciplinary projects.